The Personal Presence of the Preacher in Preaching: An Explorative Study on Self-Disclosure in Sermons at Pentecost (Homiletic, 2020)
How does self-disclosure work in preaching? This study explores that question empirically, using a variety of data collection methods such as sermon analysis, focus groups, and interviews. Self-disclosure is an ambiguous concept in homiletical and theological literature, and it remains an ambiguous concept when considered from an empirical approach. Our focus is on how self-disclosure works brings to the fore three different homiletical processes: negotiating homiletical space, shaping the homiletical relationship, and performing self-disclosure. This study argues that researching implicit self-disclosure provides a better, though more complex, way of understanding the public presence of the preacher, than an analysis of the explicit use of the first pronoun “I” in preaching.